Species diversity of ostracods (Crustacea: Ostracoda) from rice fields in Northeast Thailand, with the description of a new Tanycypris species - Savatenalinton, Sukonthip (Zootaxa, 2017)
The species diversity of ostracods in rice fields from Northeast Thailand was studied. Fifty-two samples were collected from 43 rice fields during 2010–2016. This investigation revealed 23 genera and 52 species, including one new to science (Tanycypris eugenkempfi n. sp.) and 21 endemic species: endemic to the Oriental region (14 species), Southeast Asia (two species) and Thailand (five species). In addition, two species that were restricted to rice fields in this study were recognized: Bradleytriebella tuberculata (Hartmann, 1964) and Notodromas sinensis Neale & Zhao, 1991. The most diverse genus was Pseudostrandesia, followed by Strandesia with eight and five species, respectively. The most widely distributed species were Pseudocypretta maculata Klie, 1932 and Strandesia kraepelini (G.W. Müller, 1906) occurring in 48.8 % of the total of surveyed rice fields. The number of species in individual rice fields ranged from none to 18. Most of the samples contained three species, but one rice field showed very high species richness (18 species). Most of the species recorded in this study were also found in several types of water bodies and reported from several zoogeographical regions. The main distinguishing characters between Tanycypris eugenkempfi n. sp. and other Tanycypris species are the more tumid carapace in dorsal view, the distinctly arched dorsal margin of the carapace in lateral view, the presence of a subapical dorsal seta on the first segment of the first antenna, the smooth large bristles on the third endite of the maxillula, the absence of c-seta on the first thoracopod, and the long proximal claw (Gp) of the caudal ramus.